2015
DOI: 10.1016/j.jfluchem.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles protected by fluorinated ligands: Syntheses, properties and applications

Abstract: Abstract:The development of fluorinated gold nanoparticles is presently arising and increasing attention across several fields of nanotechnology. The synthetic approaches evolved over time from the use of almost perfluorinated alkanethiols and perfluorinated arylthiols to amphiphilic fluorinated thiols capable of ensuring solubility in conventional organic solvents and water. The interest in these systems stems from the unique properties of both nanosized and fluorous compounds. In perspective, the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…6 Some research groups have focused their attention on the synthesis of nanoparticles (NPs) decorated with fluorinated ligands to increase the local concentration of fluorine. 10 The group of Pasquato synthesised gold NPs coated with either thiolated PFCs modified with ethylenglycol moieties 11 or perfluorinated ethylenglycol 2 | J. Name., 2012, 00, 1-3 This journal is © The Royal Society of Chemistry 20xx…”
mentioning
confidence: 99%
“…6 Some research groups have focused their attention on the synthesis of nanoparticles (NPs) decorated with fluorinated ligands to increase the local concentration of fluorine. 10 The group of Pasquato synthesised gold NPs coated with either thiolated PFCs modified with ethylenglycol moieties 11 or perfluorinated ethylenglycol 2 | J. Name., 2012, 00, 1-3 This journal is © The Royal Society of Chemistry 20xx…”
mentioning
confidence: 99%
“…Boccalon et al [60] have reported the synthesis of a dual fluorescence/ 19 F MRI probe composed of fluorinated amphiphilic ligands, protecting gold nanoparticles, to which several ligand-dyes 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 Article Body Template can be introduced. In 2015, Pengo et al [61] have reviewed an overall description of different fluorinated gold nanoparticles as well as their properties and possible applications.…”
Section: Fluorinated Nanoparticles (Silica Gold)mentioning
confidence: 99%
“…Since their first description, 1 thiol self-assembled monolayers (SAM) on gold surfaces and nanoparticles have been widely used in a variety of technological applications, [2][3][4][5][6][7][8][9][10][11][12][13] and studied with a wealth of diffraction, 14-18 spectroscopic 8, [19][20][21][22][23] and other surface science techniques. 24 In addition, thiol SAMs have been modeled theoretically by several ab initio (mainly density functional theory, DFT) [25][26][27][28][29][30][31][32] and molecular mechanics 27,28,[33][34][35][36][37][38] studies.…”
Section: Introductionmentioning
confidence: 99%